2019
DOI: 10.1111/and.13394
|View full text |Cite
|
Sign up to set email alerts
|

The role of propolis against paclitaxel‐induced oligospermia, sperm abnormality, oxidative stress and DNA damage in testes of male rats

Abstract: Paclitaxel (taxol) is one of the most powerful anticancer drugs but it possesses toxic effects on male reproductive system. Propolis, from folkloric remedy, have antioxidant, anti‐inflammatory and anticancer effects. The present study established to examine the protective impact of Propolis against malformation of semen induced by taxol. Twenty‐four male rats equally divided into four groups. Group I (normal control); group II, administrated Propolis alone; group III, taxol‐treated group received taxol; group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…In previous studies, the effect of nano-selenium on testicle tissues, in which oxidative damage was induced with CP, was examined and it was determined that nano-selenium increased antioxidant enzyme activities in testicle tissue [ 62 ]. In a study, which was injected as intraperitoneal at a dose 5 mg/kg of Paclitaxel diluted in 1 mL saline once a week for four weeks, it was reported that it caused increases in 8—OHdG and DNA damage according to the control group in rats, but administration of propolis, at a dose of 50 mg/kg dissolved in 1 mL distilled water orally once daily for four weeks, alleviated the toxic effect of Paclitaxel by diminishing oxidation state and DNA damage, preserving cell energy [ 63 ]. The content of the ration used in the study is given in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the effect of nano-selenium on testicle tissues, in which oxidative damage was induced with CP, was examined and it was determined that nano-selenium increased antioxidant enzyme activities in testicle tissue [ 62 ]. In a study, which was injected as intraperitoneal at a dose 5 mg/kg of Paclitaxel diluted in 1 mL saline once a week for four weeks, it was reported that it caused increases in 8—OHdG and DNA damage according to the control group in rats, but administration of propolis, at a dose of 50 mg/kg dissolved in 1 mL distilled water orally once daily for four weeks, alleviated the toxic effect of Paclitaxel by diminishing oxidation state and DNA damage, preserving cell energy [ 63 ]. The content of the ration used in the study is given in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated the beneficial effects of AM in paclitaxel‐induced testicular injury. It is reported that paclitaxel‐induced testicular damage is characterised by cell apoptosis, abnormal spermatozoa, testicular DNA fragmentation and infertility (Abd‐Elrazek et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel demonstrates positive therapeutic impacts in the treatment of many cancer types in clinical oncology practice. However, it causes damage to multiple organs, including the testes (Abd‐Elrazek et al., 2020). After paclitaxel administration, pathological changes can be seen in the testes together with diminished spermatozoa activity (Borovskaya et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bees use Prop to cover hive walls, fill gaps, and embalm killed invader insects [11]. Propolis is a natural product that gained attention as folk medicine due to its chemical composition as it contains a variety of flavonoids, phenols, alcohols, terpenes, sterols, vitamins, and amino acids [12]. Several studies demonstrated the antibacterial, antifungal, anti-inflammatory, antioxidant, immunomodulatory, and wound healing properties of propolis extract [13].…”
Section: Introductionmentioning
confidence: 99%